2022
DOI: 10.31254/jahm.2022.8307
|View full text |Cite
|
Sign up to set email alerts
|

Morpho-Anatomical, Preliminary Phytochemical and Hptlc Profile of Extra-Pharmacopoeial Herb Passiflora foetida Linn. Leaf

Abstract: Background: Medicine has evolved after a lot of trial and error practices. Ayurveda is a life science which is meant for well-being of all living creature. The medicinal importance of wide range of plants has been recorded in Ayurveda, but some plants which are found later or exotic are not mentioned in Ayurveda, they are named as Anukta which means untold. Ethnobotany is the branch of botany which deals with the study of relationship between people and plants. Passiflora foetida Linn. is an extra pharmacopeia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
0
0
Order By: Relevance
“…It has been reported that all parts of P. foetida such as leaf, root, stem and fruit have tremendous medicinal properties, making the plant a hot spot for new drug discovery in the pharmaceutical industry (CABI, 2013). Pandith et al (2022) reported that traditionally, healers use the plant to address conditions such as asthma, skin diseases, digestive issues and headaches.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that all parts of P. foetida such as leaf, root, stem and fruit have tremendous medicinal properties, making the plant a hot spot for new drug discovery in the pharmaceutical industry (CABI, 2013). Pandith et al (2022) reported that traditionally, healers use the plant to address conditions such as asthma, skin diseases, digestive issues and headaches.…”
Section: Introductionmentioning
confidence: 99%